MANAJEMEN PUBLIK DALAM PENGENDALIAN DAN PENGAWASAN PEREDARAN OBAT KERAS: (Studi di Badan Pengawas Obat dan Makanan (BPOM) Surabaya) - Aditiya Ayoga , Muhammad; Yumarni, Tri; Haris Wanto, Alfi (Jurnal Administrasi Publik, 2025)
Management in the Control and Supervision of Prescription Drug Distribution: A Case Study at the Food and Drug Supervisory Agency (BPOM) Surabaya. This study aims to analyze the implementation of public management in the control and supervision of prescription drug distribution at the Surabaya Regional Office of the Food and Drug Supervisory Agency (BBPOM). The research background is based on the high circulation of illegal prescription drugs, especially those sold online without official distribution permits. This study employs a descriptive qualitative approach with data collection techniques including interviews, observations, and document analysis. Data analysis is conducted using a historical-comparative method. The findings indicate that BPOM Surabaya has implemented various control and supervision strategies, such as the use of information technology, public education campaigns, and strict enforcement of regulations. Supporting factors include national regulatory support, inter-agency synergy, and the commitment of supervisory personnel. However, challenges remain, including limited human resources, rapid technological advancements exploited by illegal actors, and low public awareness. These findings underscore the importance of strengthening collaborative and adaptive public management in the supervision of prescription drug distribution to protect public health on a broader scale.